The Importance of Intraoperative Selenium Blood Levels on Organ Dysfunction in Patients Undergoing Off-Pump Cardiac Surgery: A Randomised Controlled Trial - Stevanovic, Ana (Public Library of Science, 2014)
INTRODUCTION: Cardiac surgery is accompanied by an increase of oxidative stress, a significantly reduced antioxidant (AOX) capacity, postoperative inflammation, all of which may promote the development of organ dysfunction and an increase in mortality. Selenium is an essential co-factor of various antioxidant enzymes. We hypothesized a less pronounced decrease of circulating selenium levels in patients undergoing off-pump coronary artery bypass (OPCAB) surgery due to less intraoperative oxidative stress. METHODS: In this prospective randomised, interventional trial, 40 patients scheduled for elective coronary artery bypass grafting were randomly assigned to undergo either on-pump or OPCAB-surgery, if both techniques were feasible for the single patient. Clinical data, myocardial damage assessed by myocard specific creatine kinase isoenzyme (CK-MB), circulating whole blood levels of selenium, oxidative stress assessed by asymmetric dimethylarginine (ADMA) levels, antioxidant capacity determined by glutathionperoxidase (GPx) levels and perioperative inflammation represented by interleukin-6 (IL-6) levels were measured at predefined perioperative time points. RESULTS: At end of surgery, both groups showed a comparable decrease of circulating selenium concentrations. Likewise, levels of oxidative stress and IL-6 were comparable in both groups. Selenium levels correlated with antioxidant capacity (GPx: r = 0.720; p<0.001) and showed a negative correlation to myocardial damage (CK-MB: r = −0.571, p<0.001). Low postoperative selenium levels had a high predictive value for the occurrence of any postoperative complication. CONCLUSIONS: OPCAB surgery is not associated with less oxidative stress and a better preservation of the circulating selenium pool than on-pump surgery. Low postoperative selenium levels are predictive for the development of complications. TRIAL REGISTRATION: ClinicalTrials.gov NCT01409057